Open Access and Open Data at CGIAR: challenges and solutions - Devare, Medha; Zandstra, Megan; Clobridge, Abby; Fotsy, Michelle; Abreu, David; Arnaud, Elizabeth; Baraka, Paul; Bonaiuti, Enrico; Chukka, Srinivasa Rao; Dieng, Ibnou; Dreher, Kate; Erlita, Sufiet; et al. (2017)
CGIAR is a global research partnership of 15 geographically and scientifically diverse Centers dedicated to reducing poverty, enhancing food and nutrition security, and improving natural resource management. The Centers are charged with accelerating innovation to tackle challenges at a variety of scales from the local to the global. This requires data and other research outputs to be findable, accessible, interoperable, and reusable – that is, open via FAIR principles, and inter-linked where relevant. CGIAR Centers have made strong progress in implementing publication and data repositories; however, many of these still represent silos whose contents are not generally easily discoverable or inter-linked (e.g., agronomic trial data with socioeconomic or adoption data in the same geographies). In the absence of such interoperability-mediated discovery, “open” is of limited utility. The overall goal is for CGIAR’s trove of research data and associated information to be indexed and interlinked through a demand-driven cyberinfrastructure for agriculture, ensuring that research outputs are discoverable by humans and machines, and reusable via appropriate licensing to enhance innovation, uptake and impact. There are challenges to achieving this goal, not only across CGIAR, but for the agricultural domain in general. Among the foremost hurdles is that “open” tends to remain an unfunded mandate, making it difficult to operationalize effectively. Further, there is still significant concern on the part of scientists about making data open – largely centered around issues of trust, time, and quality – resulting in repositories frequently exposing metadata rather than the data sets themselves. While the ability to find metadata about resources qualifies as improvement, it continues to impose barriers to data access, discoverability, integration, and analysis, without which complex challenges to global agriculture development cannot be effectively addressed. CGIAR is addressing the urgent need to create a data sharing culture and enabling environment for Open Access and Open Data (OA/OD) that includes projects planning for OA/OD and allocating funds to support it, in parallel with the technical infrastructure mentioned above. While the technology necessary to enable FAIR outputs exists, achieving success implies data provider and consumer trust and buy-in, agreement and adherence to interoperability standards and/or mapping across varied approaches, and compliance with guidelines (including those on citation and licensing governing content reuse). Agricultural institutions, including CGIAR, are only now beginning to address these issues systematically, to agree on and adopt standards-based systems and processes, and to build cross-walks across differing schemas. Through its Open Access and Open Data initiative funded by the Bill and Melinda Gates Foundation, and via plans for an ambitious Big Data and ICT Platform , CGIAR is developing technical and cultural approaches that will enable research content to be consistently and seamlessly discovered, interlinked, and analyzed across its Centers. This paper describes the strategy used to identify the specific contexts and challenges faced by Centers in building an infrastructure and culture for OA/OD across CGIAR, with the ultimate goal of achieving greater impact in agricultural research for development.